Acceleration of western Arctic sea ice loss linked to the Pacific North American pattern - Zhongfang Liu (Nature Portfolio, 2021)
The fastest sea-ice decline has been observed in the western Arctic, but the underlying mechanisms are still unclear. Here, the authors show that the Pacific North American pattern plays an important role in western Arctic sea-ice variability.